2002
DOI: 10.1002/art.10139
|View full text |Cite
|
Sign up to set email alerts
|

A six‐month randomized, controlled, double‐blind, dose‐response comparison of intravenous pamidronate (60 mg versus 10 mg) in the treatment of nonsteroidal antiinflammatory drug–refractory ankylosing spondylitis

Abstract: Objective. To determine the safety and efficacy of intravenous (IV) pamidronate treatment in ankylosing spondylitis (AS) patients who have had a suboptimal response to nonsteroidal antiinflammatory drugs (NSAIDs).Methods. Pamidronate at 60 mg was compared with pamidronate at 10 mg rather than placebo in view of the high incidence of transient arthralgias upon first IV exposure to the drug. The drug were given monthly for 6 months in a randomized, double-blind, controlled trial. The inclusion criterion was acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
69
0
16

Year Published

2003
2003
2009
2009

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 205 publications
(88 citation statements)
references
References 35 publications
3
69
0
16
Order By: Relevance
“…However, there are certain drugs or groups of drugs that have been shown in clinical studies to be connected with ADRs in the joints, e.g., bisphosphonates (1,2).…”
Section: Introductionmentioning
confidence: 99%
“…However, there are certain drugs or groups of drugs that have been shown in clinical studies to be connected with ADRs in the joints, e.g., bisphosphonates (1,2).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, there is evidence that, in some instances, these agents may reduce inflammation. The reduction in systemic signs of inflammation has been particularly dramatic in patients with ankylosing spondylitis (AS) (30)(31)(32)(33). For example, in a recent trial, investigators demonstrated that 6 months of therapy with pamidronate resulted in improved clinical, laboratory, and radiologic parameters of disease activity (30).…”
mentioning
confidence: 99%
“…The reduction in systemic signs of inflammation has been particularly dramatic in patients with ankylosing spondylitis (AS) (30)(31)(32)(33). For example, in a recent trial, investigators demonstrated that 6 months of therapy with pamidronate resulted in improved clinical, laboratory, and radiologic parameters of disease activity (30). High doses of pamidronate were used in that study, which may have resulted in unique effects on immune or inflammatory cell function that may be distinct from the effects on osteoclasts or other bone cell types.…”
mentioning
confidence: 99%
“…We read with great interest the article by Maksymowych et al (1). The only complication associated with pamidronate therapy in their study was transient arthralgias/ myalgias after the first intravenous (IV) infusion.…”
Section: To the Editormentioning
confidence: 98%